1991
DOI: 10.1104/pp.97.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diphenyl Ether Herbicides on Oxidation of Protoporphyrinogen to Protoporphyrin in Organellar and Plasma Membrane Enriched Fractions of Barley

Abstract: In barley (Hordeum vulgare L.) root cells, activity for oxidizing protoporphyrinogen to protoporphyrin (protoporphyrinogen oxidase), a step in chlorophyll and heme synthesis, was found both in the crude mitochondrial fraction and in a plasma membrane enriched fraction separated by a sucrose gradient technique utilized for preparing plasma membranes. The herbicides to increase greatly the intracellular levels of the photodynamic tetrapyrrole, protoporphyrin, causing light dependent phytotoxic effects (2-4, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0
4

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 29 publications
5
98
0
4
Order By: Relevance
“…Our data are in general agreement with the model of Jacobs et al (1991), in which it was hypothesized that plastid Protox is inhibited by AFM, whereas a PM-associated Protox-like activity is unaffected. This hypothesis helps to explain how inhibition of an enzyme can cause the product to accumulate in vivo.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our data are in general agreement with the model of Jacobs et al (1991), in which it was hypothesized that plastid Protox is inhibited by AFM, whereas a PM-associated Protox-like activity is unaffected. This hypothesis helps to explain how inhibition of an enzyme can cause the product to accumulate in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…Much of the porphyrin fluorescence appeared to be associated with the PM. Enzymic data of Jacobs et al (1991) supported this conclusion. They found that, although AFM strongly inhibited etioplast Protox in vitro, a Protox-like activity of a PM-enriched fraction was almost unaffected by the herbicide.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…[4][5][6][7] The acute toxicity of oxyfluorfen is a result of the accumulation of Protogen IX, which is oxidized in the cytoplasm to Proto IX by a nonspecific plasma membrane-bound peroxidase. 8,9) Proto IX in the cytoplasm is not metabolized by the porphyrin biosynthetic pathway because Mg-chelatase and Fe-chelatase, which use Proto IX as a substrate, are located in chloroplasts and mitochondria. Cytoplasmic Proto(gen) IX, a potent photosensitizer, absorbs light that is used in detrimental reactions.…”
Section: Introductionmentioning
confidence: 99%